Impact of the COVID-19 pandemic on the education and health of university students - Lira Neto, José Cláudio Garcia; Sáber, Ana Júlia Gancedo; Roza, Mayara Pinheiro da; Freitas, Maria Bárbara Todisco de; Grifante, Leonardo; Fernandes, Bruna Karen Cavalcante; Penha, Jardeliny Corrêa da (Revista de Enfermagem da UFPI, 2024)
Objective: To analyze the impact of the COVID-19 pandemic on the education and health of university students. Methods: Cross-sectional study, carried out with 163 university students from different courses, between May and December 2022, in São Paulo, Brazil. Google Forms was used to capture information related to academic dynamics during the COVID-19 pandemic. Results: The majority of students were women and in the health field, studying their third year of college. 53.1% of students considered online classes to be bad or terrible, but only 43.6% thought about giving up their studies during the period. Most participants spent between five and nine hours a day studying in front of screens, and 57.7% said they experienced a drop in academic performance. Students had problems sleeping (58.2%, p<0.001), increased moments of stress, fatigue, depression, or anxiety (76.7%, p<0.001), felt hopeless (71.7%, p< 0.001), and showed changes in weight during the period (75.4%, p<0.001). Conclusion: The COVID-19 pandemic had negative impacts on the majority of those investigated, both in education and health, especially mental health. It is necessary to encourage multimodal curricula and programs that encourage quality of life and mental health in university spaces.